Infant feeding practices and their association with picky eating behaviour among toddlers attending maternal and child health in Kota Bharu Kelantan - Salamon, Siti Hazar (2020)
Objectives: We undertake a research to look at the characteristics of infant feeding practices; prevalence of picky eating behaviour and their associated factors among children aged 18 to 24 months attending the maternal and child health (MCH) clinics in Kota Bharu, a city in northeast Peninsular Malaysia. Methods: This was a cross-sectional study conducted from July to September 2019. Data was collected via interview using structured questionnaire contained demographic data of toddlers and caretakers, characteristic of infant feeding practices and picky eating behaviour. Logistic regressions were used for data analysis and the results were presented by adjusting odds ratios with 95% confidence intervals. Results: Three hundred and two (302) toddlers were involved in this study. Breastfeeding was initiated within the first hour of birth for the majority of infants (72%), 65% continued the exclusive breastfeeding for six months; 63% up till one year old and 45% by 18 to 24 months old. The majority (86.1%) were weaned at 4 to 6 months old. In this sense, 79% was found to have at least one picky eating behaviour; food neophobia 19%, food rejection 36%, tendency for preferring specific food preparation method 52% and limited variety of food 48%. Factors found to be independently associated with picky eating behavior include (1) delayed initiation of breastfeeding after delivery with food rejection (p=0.007) (2) father’s low income with preference for specific food (p=0.015) (3) father’s children more than five with eating limited variety of food (p=0.007) (4) types of weaning foods; semisolid food vs blended food with food rejection (p=0.006) (5) serving of dessert and candies with preference for specific food (p<0.001). Conclusions: The prevalence of picky eating behaviour is high at 79%. The associated factors include delayed breastfeeding initiation after birth, low parental income and parents with children more than five, the use of semisolid for weaning, and serving sweet foods such as candies as part of the weaning diets.